2020
DOI: 10.3390/microorganisms8040518
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based Quantitative Proteomics Analysis Identifies Host Pathways Modulated during Toxoplasma gondii Infection in Swine

Abstract: Toxoplasma gondii is a leading cause of foodborne illness and consumption of undercooked pig meat is a major risk factor for acquiring toxoplasmosis, which causes a substantial burden on society. Here, we used isobaric tags for relative and absolute quantification (iTRAQ) labelling coupled with liquid chromatography-tandem mass spectrometry (LC-MS/MS) to identify cellular proteins and pathways altered during T. gondii infection in pigs. We also used parallel reaction monitoring-based LC-MS/MS to verify the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Notwithstanding, this gene has been reported by several studies to be differently methylated in preterm cord blood samples; at this time its role in PTB still remains largely unexplored. However, a recent paper reported that PLCH1 expression can be modulated during toxoplasma gondii infection [ 20 ] and this finding is interesting if we consider that congenital toxoplasmosis can be a cause of preterm birth [ 21 ]. FOXK1 gene is a transcription factor of the forkhead box family (transcription factors that play important roles in regulating the expression of genes involved in cell growth, proliferation, differentiation, and longevity).…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, this gene has been reported by several studies to be differently methylated in preterm cord blood samples; at this time its role in PTB still remains largely unexplored. However, a recent paper reported that PLCH1 expression can be modulated during toxoplasma gondii infection [ 20 ] and this finding is interesting if we consider that congenital toxoplasmosis can be a cause of preterm birth [ 21 ]. FOXK1 gene is a transcription factor of the forkhead box family (transcription factors that play important roles in regulating the expression of genes involved in cell growth, proliferation, differentiation, and longevity).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to humans, T. gondii infection is usually asymptomatic in pigs. As observed in previous studies, some animals may develop mild clinical signs, such as fever, apathy or lack of appetite, during the acute phase of the disease and fully recovering during the chronic phase (4,(6)(7)(8)(9). Although clinical toxoplasmosis in swine is rare, outbreaks of toxoplasmosis in pigs have been reported in China and Brazil (10,11).…”
Section: Introductionmentioning
confidence: 73%
“…Host-parasite interactions during T. gondii infection in livestock species such as pigs have not been sufficiently studied (4,(6)(7)(8)(9). Here, we examined the interaction of T. gondii and piglets as well as the potential effect of two genotypes on the development of the disease (clinical outcome, immune response and parasite dissemination) and finally the persistence of the parasite in target tissues during the chronic phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different technologies have been used to study the molecular attributes of T. gondii, and the molecular mechanisms associated with T. gondii infection in different hosts, including proteomics [10][11][12], transcriptomics [13][14][15], and metabolomics [16][17][18]. Over the past decade, proteomic approaches have been widely used to improve the understanding of host-pathogen interactions [19,20].…”
Section: Introductionmentioning
confidence: 99%